The Impact of Anthropological Machine on Women and Non-Human Animals: A Study of Coetzee’s Disgrace (Global Journal of Human-Social Science, 2022)
This article unfolds the impact the anthropological machine on women and non-human animals in J M Coetzee s Disgrace The research method implemented in this article includes the post-humanist view that dismantles the divide between humans and non-human animals Consequently the study discovers the bare life of both non-human animals and women through the process of inclusion and exclusion So this research output clarifies the unethical practice of men which has dichotomized society into a human and non-human world The conclusion drawn from this study displays how the animalization of women is parallel to the animalization of non-human animals
Keywords: anthropological machine; animalization; bare life; biopolitics; posthumanism; impact